2005
DOI: 10.1111/j.1365-294x.2005.02815.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by distance and gene flow in the Eurasian badger (Meles meles) at both a local and broad scale

Abstract: Eurasian badgers, Meles meles, have been shown to possess limited genetic population structure within Europe; however, field studies have detected high levels of philopatry, which are expected to increase population structure. Population structure will be a consequence of both contemporary dispersal and historical processes, each of which is expected to be evident at a different scale. Therefore, to gain a greater understanding of gene flow in the badger, we examined microsatellite diversity both among and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 110 publications
11
86
3
Order By: Relevance
“…Overall, the genetic diversity within the British population was not substantially less than that of the Swiss population, corroborating conclusions by Pope et al (2006). A large number of loci deviated from HardyWeinberg genotypic proportions in the UK population.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Overall, the genetic diversity within the British population was not substantially less than that of the Swiss population, corroborating conclusions by Pope et al (2006). A large number of loci deviated from HardyWeinberg genotypic proportions in the UK population.…”
Section: Discussionsupporting
confidence: 69%
“…However, the 16 loci used in the present study were developed from individuals captured in Woodchester Park (Carpenter et al, 2003), in which no systematic heterozygote deficiencies were observed when performing analyses on adults and cubs separately (Carpenter et al, 2005). The deviations from Hardy-Weinberg proportions are therefore not an intrinsic characteristic of these loci (see also Frantz et al, 2004;Pope et al, 2006), but very likely the result of the strong spatial autocorrelation pattern observed in the UK study area (Frantz et al, 2009). Loiselle's F ij , the measure of kinship coefficient used, does not assume that loci conform to Hardy-Weinberg genotypic proportions (Vekemans and Hardy, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…American badger's tolerance for fragmentation and overall high gene flow differs greatly from the more well-studied European badger (Meles meles) populations in the United Kingdom and Ireland. In European badgers, multiple authors have recorded evidence for restricted dispersal owing to both natural (that is, rivers; Sleeman et al, 2009;Frantz et al, 2010b) and anthropogenic (roads; Clark et al, 1998;Frantz et al, 2010a) barriers, as well as strong fine-scale IBD created by philopatry within dense populations (Pope et al, 2006;Frantz et al, 2010a). American badgers, in contrast, do not avoid large roads (Apps et al, 2002), do not form social groups and occur at lower densities than UK badger populations, so the difference in gene flow patterns likely stems from their disparate ecologies.…”
Section: Landscape Genetics Of Badgers In Wisconsinmentioning
confidence: 99%
“…It is now well established that the European badger is one of the four Eurasian badger species (Del Cerro et al, 2010 and references therein). The broad-scale genetic structure of the European species is of interest, as it may be the result of historic restriction to and expansion from glacial refugia and/or recent impact by extensive anthropogenic interference (Pope et al, 2006). Indeed, badger densities declined in some European countries owing to the large-scale gassing of setts during the rabies control campaigns of the 1960s and 1970s (Griffith and Thomas, 1997).…”
Section: Introductionmentioning
confidence: 99%